2013
DOI: 10.4315/0362-028x.jfp-12-271
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Cross-Contamination Transfer Dynamics at a Mock Retail Deli Market Using GloGerm

Abstract: Ready-to-eat (RTE) deli meats are considered a food at high risk for causing foodborne illness. Deli meats are listed as the highest risk RTE food vehicle for Listeria monocytogenes. Cross-contamination in the retail deli market may contribute to spread of pathogens to deli meats. Understanding potential cross-contamination pathways is essential for reducing the risk of contaminating various products. The objective of this study was to track cross-contamination pathways through a mock retail deli market using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 41 publications
1
13
0
1
Order By: Relevance
“…A mock retail deli study (15) was conducted, in which known sites were contaminated using an abiotic surrogate (GloGerm); it was observed that initial glove and initial sheer blade contamination spread the surrogate across the most sites. This study serves as a control of the conceptual model shown in Figure 1 and mass transfers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A mock retail deli study (15) was conducted, in which known sites were contaminated using an abiotic surrogate (GloGerm); it was observed that initial glove and initial sheer blade contamination spread the surrogate across the most sites. This study serves as a control of the conceptual model shown in Figure 1 and mass transfers.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted research was commissioned and data were acquired to fill the specific data needs o f this risk assessment (e.g., 9,14,15). In addition, data, predictive microbial models, and doseresponse models were extracted from the literature directly or via meta-analyses (e.g., 5,7,10,16,35,37).…”
Section: Methodsmentioning
confidence: 99%
“…cross-sectional or minimal longitudinal evaluation). Two studies have also investigated potential cross-contamination dynamics in mock delis using fluorescent powder or liquid surrogates for L. monocytogenes (9,19). In these studies, mock deli environments were created to investigate directionality and quantitate transmission of GloGerm under nonnal deli activities (e.g., volunteers performed common deli tasks, such as slicing, weighing, packaging, and serving products to customers) under different contamination source scenarios.…”
mentioning
confidence: 99%
“…Mechanical slicers pose cross-contamination risks in delis and are an important source of L. monocytogenes cross-contamination and growth (7, 11, 12, 14, 15). This pathogen can adhere to stainless steel, making deli slicers a suitable environment for pathogen contamination and growth (13).…”
mentioning
confidence: 99%